2020
DOI: 10.1177/1756284820934315
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota transplantation in Clostridioides difficile infection: real-life experience from an academic Italian hospital

Abstract: Background: Faecal microbiota transplantation (FMT) is a reasonable therapeutic option for the treatment of Clostridioides difficile infection (CDI) recurrent and refractory (RCDI) to therapy, but little evidence on the long-term impact of this therapy is currently available in the literature. The aim of this study was to evaluate the efficacy and safety of FMT in recurrent and refractory CDI and the modifications of the recipient’s gut microbiota in the medium–long term. Methods: This prospective study collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…15 The study reported significant change in microbiota toward eubiotic status at all time points analyzed. 15 In particular, there was a decrease in protobacteria which is related to dysbiosis and normalization of Faecalibacterium parusnitizii 1 year post FMT again favoring eubiotic state achieved by FMT. 15 When compared with standard oral antibiotic treatment, FMT has demonstrated survival benefit.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…15 The study reported significant change in microbiota toward eubiotic status at all time points analyzed. 15 In particular, there was a decrease in protobacteria which is related to dysbiosis and normalization of Faecalibacterium parusnitizii 1 year post FMT again favoring eubiotic state achieved by FMT. 15 When compared with standard oral antibiotic treatment, FMT has demonstrated survival benefit.…”
Section: Introductionmentioning
confidence: 81%
“… 13 , 14 A prospective study conducted by Barberio et al analyzed stool samples for metagenomic analysis pre- and post-FMT at 1 week and 6 and 12–24 months. 15 The study reported significant change in microbiota toward eubiotic status at all time points analyzed. 15 In particular, there was a decrease in protobacteria which is related to dysbiosis and normalization of Faecalibacterium parusnitizii 1 year post FMT again favoring eubiotic state achieved by FMT.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent study based on deep analysis and mouse studies provided support for the hypothesis that specifically bile salt hydrolase-producing bacteria contribute to the success of the FMT in recurrent C. difficile infections, as this enzyme can degrade taurocholic acid, a potent C. difficile germinant (Mullish et al, 2019). Of interest, some reports indicate that subsequent disturbances of FMT-treated patients, such as those evoked by the use of antibiotics, may compromise the microbiota and result in a relapse with non-C. difficile-dependent colitis that subsequently needed to be corrected by a new FMT (Barberio et al, 2020;Satokari et al, 2014). This situation is reminiscent of a non-resilient microbiome in a metastable equilibrium that can return to an alternative stable state associated with inflammation.…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…FMT resembles the most direct approach to restore gut dysbiosis currently available in clinical and experimental practice. It consists in the infusion of feces from a healthy donor directly to the gastrointestinal tract of the recipient, restoring both the complexity and diversity of the gut microbiota [46][47][48]. From a bench point of view, FMT has also been associated with a reduction of antimicrobial resistance genes in stool microbiota [49].…”
Section: Beyond Probiotics: Fecal Microbiota Transplantation (Fmt)mentioning
confidence: 99%